Dense type rock-filled roadbed structure and construction method thereof

By setting up isolation layers and closed slopes in the stone-filled roadbed, the problems of high porosity and poor deformation stability of the traditional stone-filled roadbed are solved, and the density and stability of the roadbed are improved, extending the service life cycle and reducing maintenance costs.

CN119824745APending Publication Date: 2025-04-15SHANDONG EXPRESSWAY INFRASTRUCTURE CONSTR CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510015218.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

Traditional stone-filled roadbeds have problems such as excessive particle size, high discreteness, and difficult to compress, resulting in a large number of pores inside the roadbed, which are prone to deformation and instability.

Method used

A dense stone filling roadbed structure is adopted, including the stone filling main structure, isolation layer and closed slope. The isolation layer consists of a stone filling body, a filling material and a isolation agent, and the sealing slope consists of a stone filling body, a filling material and a sealing agent. Through the setting of these levels, the compaction and stability of the roadbed are achieved.

Benefits of technology

It effectively reduces the internal porosity of the roadbed, improves the long-term deformation stability and bearing capacity of the roadbed, extends the service life cycle, and reduces maintenance costs during the operation period.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119824745A_ABST
    Figure CN119824745A_ABST
Patent Text Reader

Abstract

The invention discloses a dense rock-filled roadbed structure and a construction method thereof, and belongs to the field of road engineering. The rock-filled roadbed structure comprises a rock-filled main body structure, isolating layers are arranged at the bottom and the top of the rock-filled main body structure, closed side slopes are arranged on the two sides of the rock-filled main body structure and the two sides of the isolating layers, and paving is completed by adopting the process of closing firstly and then filling. Compared with the prior art, the inner pore structure of the roadbed can be effectively reduced, a dense overall structure is formed, and the method has very important practical significance for solving common problems in the design and construction process of the rock-filled roadbed and effectively reducing the risk of common engineering disasters of a traditional rock-filled roadbed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of road engineering, and specifically provides a dense stone-filled roadbed structure and a construction method thereof. Background Art

[0002] my country has a complex and diverse terrain, with mountains and hills accounting for 2 / 3 of the country's total area. In the process of mountain highway construction, in order to meet the safety, comfort and economy of road line shape, it is inevitable to have deep excavation and high filling of roadbed. Mountainous areas usually have scarce soil resources and rich stone resources. At the same time, highway construction produces a large amount of stone waste during roadbed excavation and tunneling. Therefore, stone has become an important source of filling materials for mountainous fill roadbed.

[0003] In actual engineering applications, the thickness of the stone-filled roadbed is generally 6-8 meters, and it is usually filled and compacted layer by layer in 8-10 layers. Although it can meet the road design requirements, there are still problems such as large particle size, high discreteness, and difficulty in compaction, which leads to a large number of pores inside the roadbed after filling. After long-term exposure to repeated changes in load, temperature, humidity, etc., the stone-filled skeleton will slowly weather and peel off at the edges and fulcrums, resulting in compression, creep and wetting deformation, causing the roadbed to deform and become unstable. Summary of the invention

[0004] The present invention aims at the above-mentioned deficiencies of the prior art and provides a dense rock-filled roadbed structure which can effectively reduce common engineering disasters of traditional rock-filled roadbeds.

[0005] The technical solution adopted by the present invention to solve the technical problem is: a dense stone-filled roadbed structure, including a stone-filled main structure, an isolation layer is arranged at the bottom and top of the stone-filled main structure, and closed slopes are arranged on both sides of the stone-filled main structure and the isolation layer.

[0006] The stone-filled main structure is composed of a stone-filled main body and a filling material poured into the stone-filled main body;

[0007] The isolation layer is composed of a stone filling body, and a filling material and an isolation agent poured into the stone filling body;

[0008] The closed slope is composed of a stone-filled main body, and filling materials and a sealing agent poured into the stone-filled main body.

[0009] In the roadbed structure of the present invention, the isolation layer is used for the bottom and top layers of the main structure, which can play the role of compaction, waterproofing, and anti-seepage, and reduce the impact of external moisture intrusion; the sealing layer is used for the two side parts of the main structure, and hardens in a relatively short time by accelerating the condensation effect, thereby achieving effective filling of the two side parts, which can effectively reduce the internal pore structure of the roadbed and form a dense overall structure with long-term deformation stability and continuous bearing capacity.

[0010] Preferably, the stone filling body is formed by compacting natural or processed stone materials, the uniaxial saturated compressive strength of the stone is not less than 15 MPa, the maximum controlled particle size of the stone is 800 mm, and the porosity after compaction is 10% to 40%.

[0011] Preferably, the filling material is a fluid mixture of a filling main material, a filling auxiliary material and water, wherein the filling main material is preferably fine-grained soil, stone powder and / or tailings powder; the filling auxiliary material is preferably red mud, titanium gypsum, cement, steel slag powder, granulated blast furnace powder and / or volcanic ash powder.

[0012] Preferably, the mass ratio of the main filling material, the auxiliary filling material and water in the filling material is (55-90):(10-45):(45-120), and particularly preferably (60-80):(20-40):(55-110).

[0013] Preferably, the filling material has a fluidity > 240 mm, preferably a fluidity > 260 mm.

[0014] Preferably, the maximum particle size of the main filler material is not greater than 2 mm, preferably 0.075-2 mm, and the plasticity index is not greater than 26, preferably 17-26.

[0015] Preferably, the maximum particle size of the filling auxiliary material is not greater than 0.5 mm, preferably 0.05-0.5 mm, and the specific surface area is not less than 280 m 2 / kg, preferably 280-350m 2 / kg.

[0016] Preferably, the mass ratio of the filler material to the isolation agent in the isolation layer is (80-92):(8-20), and particularly preferably (82-90):(10-18).

[0017] Preferably, the isolation agent comprises at least magnesium aluminum silicate, methyl silicic acid and sodium hexametaphosphate, and the mass ratio of magnesium aluminum silicate, methyl silicic acid and sodium hexametaphosphate is (55-70):(18-30):(6-18), and particularly preferably (60-68):(23-28):(9-18). Among them, magnesium aluminum silicate is in powder form, with a purity of ≥98%, a fineness of ≥325 mesh, and a pH value (5% aqueous solution) of 7.0-9.5; methyl silicic acid is in granular form, with a solid content of ≥54%, a silicon content of ≥22%, and an acid content (calculated as HCl) of ≤2.0; sodium hexametaphosphate is in powder or granular form, with a purity of ≥95% and a fineness of ≥60 mesh.

[0018] In the release agent, the magnesium aluminum silicate component has a trioctahedral crystal structure. When it swells in water, it forms a network gel, which is adsorbed on the surface of the filler particles and automatically disperses to form a uniform and stable slurry material. At the same time, its water dispersion system is alkaline, which stimulates the Si in the filler material to 4+ 、Al 3+ , Ca 2+ The depolymerization, polycondensation and hydration reactions form polymer products. When the methylsilicic acid component meets water, the silicon-oxygen bonds in the molecular structure break, releasing the silanol groups with water-repellent properties, forming a dense waterproof film on the surface of the solid structure of the hardened filling material, effectively improving the ability to prevent external water penetration. The sodium hexametaphosphate component contains a large number of oxygen bonds and phosphorus-oxygen bonds, which react with Ca 2+ 、Al 3+ When high-valent cations come into contact with the anions, they replace the sodium atoms in the anions and aggregate to form stable complexes through chelation, which further enhances the waterproof and anti-seepage properties of the colloidal structure on a macro scale.

[0019] Furthermore, the isolation agent may also include lithium magnesium silicate, sodium octadecanoate and / or acetylated distarch adipate. The lithium magnesium silicate can form a uniformly dispersed and stable gel slurry with the filler particles through dispersion; the stearate ions of the sodium octadecanoate combine with the cations in the slurry to form a water-insoluble compound, thereby enhancing the hydrophobic effect; and the acetylated distarch adipate can increase the slurry consistency and reduce segregation after dissolution, thereby improving the engineering performance of the isolation material.

[0020] The mass ratio of magnesium aluminum silicate, methyl silicic acid, sodium hexametaphosphate, lithium magnesium silicate, sodium octadecanoate, and acetylated distarch adipate in the isolation agent is preferably (55-70):(18-30):(6-18):(0-12):(0-10):(0-5), and particularly preferably (60-68):(23-28):(9-18):(3-8):(1-5):(0-5).

[0021] Preferably, the mass ratio of the filling material to the sealing agent in the closed slope is (75-90):(10-25), and particularly preferably (75-85):(15-25).

[0022] Preferably, the sealing agent at least comprises calcined kaolin, potassium aluminate and calcium formate, and the mass ratio of calcined kaolin, potassium aluminate and calcium formate is (50-65):(12-28):(10-24), and particularly preferably (55-60):(15-25):(15-20). Among them, the calcined kaolin has an effective ingredient content of ≥95%, a fineness of ≥325 mesh, and a moisture content of <3%; potassium aluminate is solid or liquid, and has an effective ingredient content of ≥95%; calcium formate has an effective ingredient content of ≥98%, a fineness of ≥18 mesh, and a water-insoluble content of <0.5%.

[0023] The calcined kaolin component in the sealant has an open lattice structure, which makes Si 4+ 、Al 3+ The activity is enhanced, and [SiO4] and [AlO4] are quickly dissolved in the alkaline environment of the filling material, reconstructed to form amorphous aluminosilicate, and then further condensed to form a network gel, thereby achieving coagulation and hardening. The potassium aluminate component is hydrolyzed to produce AlO2 - , and the large amount of Ca in the filling material 2+ Rapid reaction to form calcium aluminate hydrate. This process not only absorbs and combines a large amount of free water, but also the calcium aluminate hydrate continues to crystallize and grow to form a three-dimensional network structure. At the same time, the calcium formate component is dissolved in water and reacts rapidly with part of the calcium aluminate hydrate product to form needle-shaped columnar crystals, which continue to grow and develop cross-linking to form a network space secondary structure, causing the filling material to quickly lose fluidity and harden.

[0024] Furthermore, the sealant may also include sodium aluminate, calcium aluminate, potassium aluminate, hydrated calcium silicate and / or sepiolite powder. Sodium aluminate can increase the alkalinity to accelerate the hydration reaction process and promote early hardening; calcium aluminate or potassium aluminate can promote the formation of gel structure after amorphous silicate; hydrated calcium silicate has a crystal nucleus and filling effect, accelerates the gel nucleation growth of hydration products, and generates a very high surface energy to form agglomerates; sepiolite powder has a microscopic layer chain and pore structure, which effectively improves the adsorption effect and water holding performance between hydration products.

[0025] The mass ratio of calcined kaolin, potassium aluminate, calcium formate, sodium aluminate, calcium aluminate, potassium aluminate, hydrated calcium silicate and sepiolite powder in the sealant is preferably (50-65):(12-28):(10-24):(0-18):(0-4):(0-4):(0-9):(0-10), and particularly preferably (55-60):(15-25):(15-20):(0-18):(0-4):(0-4):(1-6):(3-7).

[0026] Preferably, the thickness of the isolation layer is 300 to 1000 mm, preferably 600 to 900 mm.

[0027] Preferably, the transverse width of the closed slope is 2 to 3 m, preferably 2.5 to 3 m.

[0028] A further technical task of the present invention is to provide a construction method for the above-mentioned dense stone-filled roadbed structure.

[0029] The construction method of the dense stone-filled roadbed structure comprises the following steps:

[0030] a. Level and compact the foundation of the dense rock-filled roadbed to meet the design requirements;

[0031] b. On the compacted foundation, the first layer of stone filling and compaction is carried out, with a compaction thickness of 300mm to 1000mm. The settlement difference between the last two compactions is no more than 5mm;

[0032] c. Carry out closed slope construction at both ends of the compacted first layer of stone filling body, pour the evenly stirred closed slope fluid mixture from the surface of the stone filling body until it is fully filled and surface slurry appears. The closed slope fluid mixture is a mixture of filling material and sealant. The initial setting time of the closed layer is controlled to 3 to 10 minutes, and the softening coefficient is not less than 0.8;

[0033] d. After the closed slope solidifies, an isolation layer is constructed in the middle of the first layer of stone filling. The evenly stirred isolation layer fluid mixture is poured from the surface of the stone filling body until it is fully filled and surface slurry appears. The isolation layer fluid mixture is a mixture of filling material and isolation agent. The isolation layer permeability coefficient is not greater than 1.0×10 -7 cm / s;

[0034] e. After the isolation layer solidifies, the second layer of stone filling is carried out, and the main body is filled and compacted. The construction requirements are the same as step b;

[0035] f. Carry out closed slope construction at both ends of the compacted second layer of stone filling, with the same construction requirements as step c;

[0036] g. After the closed slope solidifies, fill the middle part of the second layer of stone filling body with filling materials, and pour the evenly stirred filling material fluid mixture from the surface of the stone filling body until it is fully filled and surface slurry appears;

[0037] h. Fill in accordance with steps e to g in sequence until the penultimate layer of the designed height or layer;

[0038] i. For the last layer, first perform the main stone filling construction according to step b, and then perform the closed slope and isolation layer construction according to steps c and d respectively.

[0039] Preferably, the setting time of the closed slope is not less than 1 hour, particularly preferably 1 to 3 hours.

[0040] Preferably, the setting time of the isolation layer is not less than 6 hours, particularly preferably 6 to 8 hours.

[0041] Compared with the prior art, the compact stone-filled roadbed structure and the construction method thereof of the present invention have the following outstanding beneficial effects:

[0042] (1) The present invention uses natural or waste fine-grained materials as the main materials to develop and prepare high-flowability filling materials, which are used to fill the internal pores of the compacted stone-filled roadbed, greatly reducing the porosity index of the stone-filled roadbed, and effectively solving the undesirable engineering problems such as large internal pores, low durability, and poor deformation stability of the stone-filled roadbed;

[0043] (ii) The present invention further multi-dimensionally chemically stimulates the filling material to prepare the isolation layer and the sealing layer material, thereby realizing the isolation effect of the main structure of the stone-filled roadbed against the rise of groundwater and the intrusion of surface water, as well as the lateral rapid sealing effect, thereby forming the isolation and construction constraint of the main body of the roadbed from the external environment;

[0044] (iii) The setting of the isolation layer and the closed slope enables the stone-filled roadbed of the present invention to adopt a layered "compacting-sealing-filling" construction process, first sealing and then filling, effectively reducing the internal pore structure of the roadbed, forming a dense overall structure with long-term stable deformation and continuous bearing capacity. The method is simple and reliable in quality, and has high economic, applicability and technical advantages, and is particularly suitable for mountain road construction using large-size stone as roadbed filling material;

[0045] (IV) The internal porosity of the compact stone-filled roadbed structure of the present invention is no more than 6%, the bearing capacity attenuation of the roadbed is no more than 15%, the settlement deformation of the roadbed after construction is no more than 5%, and the long-term durability and deformation stability are greatly improved, which effectively reduces the maintenance cost during the operation period by more than 20%, and extends the service life cycle by more than 50%, with significant economic, social and environmental benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] The present invention is further described below in conjunction with the accompanying drawings.

[0047] Attached Figure 1 It is a schematic diagram of the dense stone-filled roadbed structure of an embodiment.

[0048] In the figure: 1. Main structure of stone fill, 2. Isolation layer, 3. Closed slope, 4. Main body of stone fill. DETAILED DESCRIPTION

[0049] The present invention will be further described below in conjunction with specific embodiments, but this is not intended to limit the present invention.

[0050] Embodiment 1

[0051]

Roadbed structure

[0052] As attached Figure 1 As shown, the compacted stone-filled roadbed of this embodiment is composed of a stone-filled main structure 1, an isolation layer 2, and a closed slope 3. The isolation layer 2 is located at the bottom and top of the stone-filled main structure 1. The closed slope 3 is located on both sides of the stone-filled main structure 1 and the isolation layer 2.

[0053] The designed thickness of the roadbed is 7.2m, and the single-layer compaction thickness is 900mm.

[0054]

Roadbed construction steps

[0055] a. Level and compact the foundation of the dense stone-fill roadbed to meet the design requirements.

[0056] b. On the compacted foundation, the first layer of filling and compaction of the stone filling body 4 is carried out:

[0057] The main body of the stone filling 4 is natural stone, with a uniaxial saturated compressive strength of 35MPa and a maximum controlled particle size of 600mm. After paving, a heavy roller is used for static compaction 2 times and vibration compaction 4 times. The settlement difference between the last two compactions is no more than 5mm, the compaction thickness is 900mm, and the compaction porosity measured on site is 23%.

[0058] c. Construction of closed slope 3 on both sides of the compacted first layer of stone filling body 4:

[0059] The evenly stirred closed slope fluid mixture is poured from the surface of the first layer of stone filling body 4 until the pores of the stone filling body are fully filled and surface slurry appears. The horizontal width of the closed slope is 3m, and the initial setting time is controlled to 7 to 9 minutes.

[0060] The closed slope flow mixture is a mixture of a filling material and a sealing agent, the mass ratio of the two is 78:22, and is obtained by mixing with a forced mixer for 2 minutes.

[0061] The filling material is a fluid mixture of a filling main material, a filling auxiliary material and water, which are stirred evenly. The mass ratio of each component is 75:25:105, and the fluidity is 290mm. Among them, the filling main material is silty clay (fine-grained soil), with a maximum particle size of 2mm and a plasticity index of 14.8. The filling auxiliary material is a mixture of titanium gypsum and cement in a mass ratio of 1:1, with a maximum particle size of 0.05mm and a specific surface area of ​​310m 2 / kg.

[0062] The sealing agent is prepared by uniformly mixing calcined kaolin, potassium aluminate and calcium formate, and the mass ratio of each component is 60:23:17. Among them, the calcined kaolin has an effective component content of 97.5%, a fineness of 325 meshes, and a moisture content of 1.4%; the effective component content of potassium aluminate is 98%; the effective component content of calcium formate is 98.5%, the fineness is ≥35 meshes, and the water-insoluble content is 0.3%.

[0063] d. After the closed slope solidifies (1 hour after pouring), the isolation layer is constructed in the middle part of the first layer of stone filling body 4:

[0064] The evenly stirred isolation layer fluid mixture is poured from the surface of the stone filling body until the pores of the stone filling body are fully filled and surface slurry appears. The isolation layer fluid mixture is a mixture of filling material and isolation agent, the mass ratio of the two is 82:18, and is obtained by mixing with a forced mixer for 5 minutes.

[0065] The filling material is the same as that in step c.

[0066] The release agent is prepared by uniformly mixing magnesium aluminum silicate, methyl silicic acid and sodium hexametaphosphate, and the mass ratio of each component is 65:25:10. Among them, the purity of magnesium aluminum silicate is 99%, the fineness is 400 mesh, and the pH value (5% aqueous solution) is 7.5; the solid content of methyl silicic acid is 60%, the silicon content is 25%, and the acid content (calculated as HCl) is 0.6; the purity of sodium hexametaphosphate is 97%, and the fineness is 100 mesh.

[0067] e. After the isolation layer 2 solidifies (6 hours after pouring), the second layer of stone-filled main structure 4 is filled and compacted.

[0068] Construction requirements are the same as step b

[0069] f. Carry out closed slope construction at both ends of the compacted second layer of stone filling.

[0070] Construction requirements are the same as step c.

[0071] g. After the closed slope solidifies, fill the middle part of the second layer of stone filling with filling materials:

[0072] The uniformly stirred fluid mixture of filling materials is poured from the surface of the stone filling body until the pores of the stone filling body are fully filled and surface slurry appears.

[0073] The filling material is the same as that in step c.

[0074] h. Fill in accordance with steps e to g in sequence until the seventh layer of the designed height;

[0075] i. For the 8th layer, firstly carry out the main stone filling construction according to step b, and then carry out the closed slope 3 and isolation layer 2 construction according to steps c and d respectively.

[0076] Embodiment 2:

[0077] The roadbed structure and construction method of this embodiment are basically the same as those of the first embodiment, except that the maximum controlled particle size of the natural stone material of the main body of the stone filling is 800 mm, and the compacted porosity measured on site after paving is 31%.

[0078] The second embodiment is implemented simultaneously with the first embodiment, and is constructed and tested in sections.

[0079] Embodiment three:

[0080] The roadbed structure and construction method of this embodiment are basically the same as those of the first embodiment, the only difference being the mixing ratios among the filling material, the closed slope, and the isolation layer:

[0081] The mass ratio of each component of the filler material is 65:35:100, and the fluidity is 280mm;

[0082] The mass ratio of the closed slope filling material to the sealant is 85:15;

[0083] The mass ratio of the isolation layer filling material to the isolation agent is 90:10.

[0084] The third embodiment is implemented simultaneously with the first embodiment, and is constructed and tested in sections.

[0085] Embodiment 4:

[0086] The roadbed structure and construction method of this embodiment are basically the same as those of the first embodiment, the only difference being the components of the isolation agent material and the mixing ratio between the components:

[0087] The isolation agent is prepared by uniformly mixing magnesium aluminum silicate, methyl silicic acid, sodium hexametaphosphate, lithium magnesium silicate and sodium octadecanoate, and the mass ratio of each component is 60:23:9:5:3.

[0088] The fourth embodiment is implemented simultaneously with the first embodiment, and is constructed and tested in sections.

[0089] Embodiment five:

[0090] The roadbed structure and construction method of this embodiment are basically the same as those of the first embodiment, the only difference being the components of the sealant material and the mixing ratio between the components:

[0091] The sealing agent is prepared by uniformly mixing calcined kaolin, potassium aluminate, calcium formate, hydrated calcium silicate and sepiolite powder, and the mass ratio of each component is 55:18:18:3:6.

[0092] The fifth embodiment is implemented simultaneously with the first embodiment, and is constructed and tested in sections.

[0093] [Comparative Example]

[0094] Each comparative example adopts the construction method described in Example 1, changes the settings of each structural layer and measures the roadbed-related performance indicators under different conditions.

[0095] Summary table of the configuration of each structural layer in each embodiment and comparative example:

[0096]

[0097] Comparison results of roadbed performance of various embodiments and comparative examples:

[0098]

[0099] From the comparison results, it can be seen that the dense stone-filled roadbed structure and construction method of the present invention can effectively fill the internal pores of the stone-filled roadbed to achieve a dense state, thereby greatly reducing the problems of excessive roadbed deformation and attenuation of bearing capacity caused by sliding of stone-filled particles, particle crushing, weathering, etc. At the same time, the construction difficulty can be reduced by closing and isolating the structural layer, reducing the humidity impact and scouring effect of groundwater and surface water on the inside of the roadbed, thereby improving the long-term use function, stability and durability of the stone-filled roadbed as a whole, and reducing maintenance and repair costs.

Claims

1. A dense stone-filled roadbed structure, characterized in that: It includes a stone-filled main structure, an isolation layer is arranged at the bottom and top of the stone-filled main structure, and closed slopes are arranged on both sides of the stone-filled main structure and the isolation layer. The stone-filled main structure is composed of a stone-filled main body and a filling material poured into the stone-filled main body; The isolation layer is composed of a stone filling body, and a filling material and an isolation agent poured into the stone filling body; The closed slope is composed of a stone-filled main body, and filling materials and a sealing agent poured into the stone-filled main body.

2. The dense stone-filled roadbed structure according to claim 1, characterized in that: The main body of the stone filling is made of natural or processed stone materials after compaction. The uniaxial saturated compressive strength of the stone is not less than 15MPa, the maximum controlled particle size of the stone is 800mm, and the porosity after compaction is 10% to 40%.

3. The dense stone-filled roadbed structure according to claim 1, characterized in that: The filling material is a fluid mixture consisting of a filling main material, a filling auxiliary material and water, wherein the filling main material is fine-grained soil, stone powder and / or tailings powder; the filling auxiliary material is red mud, titanium gypsum, cement, steel slag powder, granulated blast furnace powder and / or volcanic ash powder.

4. The dense stone-filled roadbed structure according to claim 3, characterized in that: The mass ratio of the main filling material, the auxiliary filling material and water in the filling material is (55-90):(10-45):(45-120), and the fluidity of the filling material is greater than 240 mm; The maximum particle size of the main filling material is not greater than 2 mm, and the plasticity index is not greater than 26; The maximum particle size of the filling auxiliary material is not greater than 0.5 mm, and the specific surface area is not less than 280 m 2 / kg.

5. The dense stone-filled roadbed structure according to claim 1, 2, 3 or 4, characterized in that: The mass ratio of the filling material to the isolation agent in the isolation layer is (80-92):(8-20), and the isolation agent includes at least magnesium aluminum silicate, methyl silicic acid, and sodium hexametaphosphate. The mass ratio of magnesium aluminum silicate, methyl silicic acid, and sodium hexametaphosphate is (55-70):(18-30):(6-18).

6. The dense stone-filled roadbed structure according to claim 5, characterized in that: Release agents also include lithium magnesium silicate, sodium octadecanoate and / or acetylated distarch adipate.

7. The dense stone-filled roadbed structure according to claim 1, 2, 3 or 4, characterized in that: The mass ratio of the filling material to the sealing agent in the closed slope is (75-90):(10-25), and the sealing agent at least includes calcined kaolin, potassium aluminate, and calcium formate. The mass ratio of calcined kaolin, potassium aluminate, and calcium formate is (50-65):(12-28):(10-24).

8. The dense stone-filled roadbed structure according to claim 7, characterized in that: The sealing agent also includes sodium aluminate, calcium aluminate, potassium aluminate, hydrated calcium silicate and / or sepiolite powder.

9. The dense stone-filled roadbed structure according to claim 1, 2, 3 or 4, characterized in that: The thickness of the isolation layer is 300 to 1000 mm; the lateral width of the closed slope is 2 to 3 m.

10. The construction method of the dense stone-filled roadbed structure according to any one of claims 1 to 9, characterized in that: The following steps are involved: a. Level and compact the foundation of the dense rock-filled roadbed to meet the design requirements; b. On the compacted foundation, the first layer of stone filling and compaction construction is carried out, with a compaction thickness of 300mm to 1000mm; c. Carry out closed slope construction at both ends of the compacted first layer of stone filling body, pour the evenly stirred closed slope fluid mixture from the surface of the stone filling body until it is fully filled and surface slurry appears, the closed slope fluid mixture is a mixture of filling material and sealant; d. After the closed slope solidifies, an isolation layer is constructed in the middle of the first layer of stone filling body, and the evenly stirred isolation layer fluid mixture is poured from the surface of the stone filling body until it is fully filled and surface slurry appears. The isolation layer fluid mixture is a mixture of filling material and isolation agent; e. After the isolation layer solidifies, the second layer of stone filling main structure is filled and compacted. The construction requirements are the same as step b; f. Carry out closed slope construction at both ends of the compacted second-layer stone-filled main structure, with the same construction requirements as step c; g. After the closed slope solidifies, fill the middle part of the second layer of stone filling body with filling materials, and pour the evenly stirred filling material fluid mixture from the surface of the stone filling body until it is fully filled and surface slurry appears; h. Fill in accordance with steps e to g in sequence until the penultimate layer of the designed height or layer; i. For the last layer, first perform the main stone filling construction according to step b, and then perform the closed slope and isolation layer construction according to steps c and d respectively.